Effects of comorbid substance use disorders on outcomes in a Housing First intervention for homeless people with mental illness. (1st August 2017) - Urbanoski, Karen; Veldhuizen, Scott; Krausz, Michael; Schutz, Christian; Somers, Julian M.; Kirst, Maritt; Fleury, Marie‐Josée; Stergiopoulos, Vicky; Patterson, Michelle; Strehlau, Verena; Goering, Paula
Abstract: Background and Aims: Evidence supports the effectiveness of Housing First (HF) programmes for people who are experiencing homelessness and mental illness; however, questions remain about its use in people with comorbid substance use disorders (SUD). The aim of this project was to test whether SUD modifies the effectiveness of an HF intervention. Design: Secondary analysis of data from a randomized controlled trial of HF versus treatment‐as‐usual (TAU) with 24‐month follow‐up, comparing those with and without SUD at trial entry. Setting: Vancouver, Toronto, Winnipeg, Moncton and Montreal, Canada. Participants: A total of 2154 participants recruited from 2009 to 2013 and randomized to HF versus TAU (67% male, mean age 40.8 ± 11.2, 25% ethno‐cultural minority). All were homeless and had a mental disorder at baseline; 35% reported symptoms consistent with SUD. Intervention: Housing paired with Intensive Case Management or Assertive Community Treatment. Measurements: Primary outcomes were days housed and community functioning. Secondary outcomes were general and health‐related quality of life and mental health symptoms. Predictors were SUD status crossed with intervention group (HF versus TAU). Findings: People with SUD in both the HF and TAU groups spent less time in stable housing, but the effect of HF did not vary by SUD status [odds ratio (OR) = 1.17, 95% confidence interval (CI) = −0.77, 1.76]. Similarly, there was no difference between those with and without SUD in the effect of HF (over TAU) on community functioning (b = 0.75, 95% CI = −0.36, 1.87), quality of life (b = −1.27, 95% CI = −4.17, 1.63), health‐related quality of life (b = −0.01, 95% CI = −0.03, 0.02) or mental health symptoms (b = 0.43, 95% CI = −0.99, 1.86). Conclusions: Housing First programs in Canada are equally effective in people with and without comorbid substance use disorder (SUD). Overall, the intervention appears to be able to engage people with SUD and is reasonably successful at housing them, without housing being contingent upon abstinence or treatment.